Analysis of Rectangular Plates on Resting Winkler and Two-Parameter Elastic Foundation Models by Finite Difference Method - Nguyen, T. H. (Engineering, Technology & Applied Science Research, 2019)
Analysis of rectangular plates on a rising elastic foundation is common when designing the foundation of civil, traffic, and irrigation works. The current research presents the results of the analysis of rectangular plates on rising Winkler elastic and two-parameter foundation using the finite difference method. The computational programming was done on Matlab. The results of the research verify the accuracy of the FEM and are in agreement with findings in the literature. In addition, this research also compares the calculation results of two foundation models and investigates the change of plate height ratio to plate size.